Detection of Hepatitis B virus Genotypes A and D Associated with liver disease in a tertiary hospital / Nur Liyana Mohamed - Mohamed, Nur Liyana (2015)
Today, hepatitis B virus (HBV) infection remains as the main etiology of liver disease worldwide. Presently, there are 10 different HBV genotypes (A to J) established with distinct geographical distribution and a discrete clinical outcome respectively. Generally, there are two genotypes predominantly high in prevalence in certain regions. Predominmt genotypes in Malaysia are genotype B and C. Currently, studies on other genotypes and their association with liver disease are not widely known. This is a preliminary study which is designed to detect hepatitis B genotype A and D in a positive HBV infected patients diagnosed with liver disease among Malaysian population. This study also aimed to find the correlation between sociodemographic data and viral loads with HBV infection and towards contribution to the progression of liver disease. In this study, 60 sermn samples collected were identified positive with HBV infection between March to April 2015 from the Kuala Lumpur Hospital were examined. However, only 35 samples were successfully genotyped. The study involved the DNA extraction process by using QIAamp® DNA Blood Mini Kit. Following, extracted DNA were analysed by real-time polymerase chain reaction (qPCR) where QuantiFast® SYBR® Green chemistry was used. Genotype A and D were detected, and the results obtained were analysed statistically. Generally, socio—demographic data might have influence on HBV infection and disease progression. However, all the stafistical analysis revealed that there is no significant association between HBV genotype A and D with age, race and gender concerning influences in advancement of liver disease. HBV viral loads also insignificantly associated with HBV genotypes A and D. This study suggested that the detection of genotype A and D will shed lights on new data for hepatitis B genotypes other than B and CA The outcomas can be referred as a new insight on HBV genotypes associated with liver disease patients in Malaysia. Further studies are required with a bigger sample size so that better understanding regarding different HBV genotypes can be achieved.